2019
DOI: 10.1177/2325967119888486
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Deep Venous Thrombosis Associated With Proximal Hamstring Rupture

Abstract: Background: Rates of deep venous thrombosis (DVT) have been studied for most common orthopaedic injuries. However, rates and risk factors have not been published for proximal hamstring injuries. Purpose: To determine the incidence of symptomatic DVT associated with proximal hamstring rupture and associations with prophylactic anticoagulation. Study Design: Case series; Level of evidence, 4. Methods: Inclusion criteria included all complete and, in a separate cohort, partial proximal hamstring ruptures treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 35 publications
0
11
1
1
Order By: Relevance
“…That said, there was no further information regarding this patient. Their VTE rate was 2.4%, which while better than Engler et al, 13 remained higher than that reported in our study.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…That said, there was no further information regarding this patient. Their VTE rate was 2.4%, which while better than Engler et al, 13 remained higher than that reported in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…Engler et al 13 reported a 6.9% incidence in their retrospective case series of 144 complete proximal hamstring ruptures, with 10 patients developing symptomatic DVTs, of which 5 were diagnosed preoperatively and 5 postoperatively. In the postoperative cohort, patients were prescribed either aspirin 325 mg twice daily or Enoxaparin 40 mg once daily.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations